Knowledge, attitude and practice of breastfeeding among mothers in a rural area of Thrissur district - Kurian, Neetha M.; Saju, C. R.; Paul, Jini Muttath (International Journal Of Community Medicine And Public Health, 2021)
Background: Universalizing early and exclusive breastfeeding is viewed as a major public health intervention to reduce the child mortality. Mothers’ knowledge and attitude towards breastfeeding may influence practices. The study intended to find the level of knowledge, attitude and practice regarding breast feeding, and factors influencing them among mothers. Methods: A cross sectional study was undertaken among all the mothers having a child of age 2 years and below. Data collection was done by interviewing a total of 710 eligible mothers, using a semi–structured validity tested questionnaire. Descriptive statistics was used for analysis. Results: The mothers had high knowledge and attitude, but poor practice levels and there exists a gap between actual and desired breast-feeding practices among them. Study has found that high knowledge and practice of breastfeeding of mothers was significantly associated (p<0.05) with their age, education, religion, socioeconomic status, parity, antenatal class on breast feeding. Positive breastfeeding attitude had significant association (p<0.05) with age, educational level and parity of the mother. A strong correlation was found to exist between knowledge and attitude scores and good correlation between attitude-practice and knowledge-practice scores of the mothers. Conclusions: Poor breastfeeding practice despite high level of knowledge and attitude was exhibited by respondents, emphasizing the need for breastfeeding intervention programs especially during antenatal and early postpartum period. Existing programs supporting breastfeeding at primary care level should be strengthened. For adherence to the correct practice of breast feeding, behavior change communication should be directed towards the family members as well.